Fluorine, Chlorine, and Bromine in Carbonate Rocks in Relation to the Chemical History of Ocean Water and Dolomitization - Williams, Harold (My University, 1969)
The purpose of this thesis is to establish possible changes in the CI/Br ratio of ancient oceans over the past 2 x 10 9 years. Variations in the Cl/Br ratio of carbonate rocks are used to indicate these changes. A secondary objective of this thesis is to determine the distribution patterns of F in limestones and dolomites. Variations in the F content of dolomites are shown to be related to environment of deposition and can be used to establish tho genesis of dolomite. The contents of the thesis include; 1) a comprehensive review of the pertinent literature, 2) a discussion of the evolution of the Cl/Br ratio of the ocean. 3) application of F in paleoenvironmental reconstruction, and 4) suggestions for further research.
Keywords: ancient oceans; carbonate rocks; ocean water; dolomitization